Milk quality testing using intelligent inference performance evaluation system integrated with IoT - Suresh Babu, G; Rama Krishna, V; Dharma Teja, V; Balraj Yadav, S (International Journal of Engineering and Technology, 2018)
One of the major used food item in day to day life is milk. Many large-scale industries are in the distribution of milk products. Quality of milk is one of the major factor in the food processing system and customers appreciate quality products. IoT is revolution and it is using extensively in our day to day life.  Our project is about maintaining the quality of the milk as it’s a perishable product. In this paper we concentrated on how the milk is depending on the different factors available in it and each one effects the quality. An attempt is made to analyze the data from the sensors with IoT used in the milk production with the help of Artificial Neural Network (ANN). The results are exhibited through an example.